HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN PERILAKU NAZHÎR DI KECAMATAN STABAT KABUPATEN LANGKAT DALAM PEMBERDAYAAN WAKAF PRODUKTIF - Hani Juliana (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2017)
The purpose of this research is to know how the relationship between Knowledge and attitude of wakaf manager who is a Nazhîr in Stabat sub-district of Langkat regency with their behavior of empowering productive endowments, focusing on knowledge relation with Nazhîr's behavior, Nazhîr attitude relationship with Nazhîr's behavior, Testing the hypothesis of Significant or not Knowledge and attitude Nazhîr against Nazhîr's behavior. While research methodology used in this research is quantitative research where the data is the number obtained from questionnaires that have been disseminated to the Nazhîr of wakaf in Stabat Sub-district.     After the research, it was found that the relationship of Knowledge to Nazhîr's Behavior is Significant while Nazhîr's Attitude is also significant towards the Behavior of Nazhîr's productive endowments in Stabat District of Langkat Regency.